Cancer-associated fibroblasts require proline synthesis by PYCR1 for the deposition of pro-tumorigenic extracellular matrix - Kay, Emily J.; Paterson, Karla; Riera-Domingo, Carla; Sumpton, David; Däbritz, J. Henry M.; Tardito, Saverio; Boldrini, Claudia; Hernandez-Fernaud, Juan R.; Athineos, Dimitris; Dhayade, Sandeep; Stepanova, Ekaterina; Gjerga, Enio; et al. (Nature metabolism, 2022)
Elevated production of collagen-rich extracellular matrix is a hallmark of cancer-associated fibroblasts (CAFs) and a central driver of cancer aggressiveness. Here we find that proline, a highly abundant amino acid in collagen proteins, is newly synthesized from glutamine in CAFs to make tumour collagen in breast cancer xenografts. PYCR1 is a key enzyme for proline synthesis and highly expressed in the stroma of breast cancer patients and in CAFs. Reducing PYCR1 levels in CAFs is sufficient to reduce tumour collagen production, tumour growth and metastatic spread in vivo and cancer cell proliferation in vitro. Both collagen and glutamine-derived proline synthesis in CAFs are epigenetically upregulated by increased pyruvate dehydrogenase-derived acetyl-CoA levels. PYCR1 is a cancer cell vulnerability and potential target for therapy; therefore, our work provides evidence that targeting PYCR1 may have the additional benefit of halting the production of a pro-tumorigenic extracellular matrix. Our work unveils new roles for CAF metabolism to support pro-tumorigenic collagen production.
Gesehen am 25.08.2022
Correction to: Nature Metabolism https://doi.org/10.1038/s42255-022-00582-0, published online 27 June 2022: In the version of this article initially published, the surname of the third author, Carla Riera-Domingo, was misspelled as Riero-Domingo. The error has been corrected in the HTML and PDF versions of the article